OP20 Perianal fistulas are characterised by expansion of interleukin-22 producing invariant natural killer T-cells and CD4+ T-cells which drive dysregulation of the extracellular matrix. (21st January 2022) - Constable, L; Iqbal, N; Cozzetto, D; Hart, A; Tozer, P; Powell, N
Abstract: Background: Perianal fistulas are a common complication of Crohn's disease (CD) affecting approximately 25% of patients, often predicting a more complicated disease course. Dysregulated immune responses and epithelial-to-mesenchymal transition (EMT) are hypothesised to contribute to fistulizing disease; however, they have been poorly studied. In this study, we investigated the immune phenotype of patients with perianal fistulizing disease and its relationship with tissue remodelling. Methods: Immune cells were isolated from fistula curettage samples (n=31) and paired peripheral blood from patients with perianal Crohn's (pCD) or idiopathic fistulizing disease. Multiparameter flow cytometry was performed to evaluate lymphocyte populations including invariant natural killer T-cells (iNKTs), gamma-delta (γδ) T-cells, CD161 + mucosal-associated invariant T-cells (MAIT), CD4 + T-cells and CD8 + T-cells. Gene expression profiling of fistula (Crohn's n=11, idiopathic n=11) and rectal tissue (Crohn's n=9, idiopathic n=9) was performed by RNA-sequencing. Cellular deconvolution of transcriptomic data using CIBERSORTx was performed to define the cellular phenotype of perianal fistulas. Cytokine treated intestinal epithelial organoids were used to probe the impact of selective cytokines on disease relevant pathways in perianal fistulas, using gene-set enrichment analysis (GSEA). Results: Perianal fistulas were characterised by expansion of iNKTs and CD4 + T-cells when compared to peripheral blood. Deeper analysis of the phenotype of these populations revealed enrichment of CD8 - CD4 - CD161 + iNKTs producing interleukin-22 (IL22), and CD4 + CD161 + T-cells producing interleukin-13 (IL13) and IL22. Surprisingly, pCD and idiopathic fistulas displayed similar immunophenotypes. Fistulas exhibited distinct transcriptional profiles to rectal tissue, although the phenotype of pCD and idiopathic fistulas appeared similar. Pathways related to the extracellular matrix (ECM) and EMT were more activated in fistulas compared to rectum. Gene-set enrichment analysis and cellular deconvolution identified an increase in the abundance of iNKTs, activated memory CD4 + T-cells, activated NK cells and neutrophils in fistula versus rectal tissue. IL13, IL22 and TNFα responsive transcripts were enriched in fistula tissue, and in the case of IL22, was shown to regulate key matrisome components. Conclusion: Perianal fistulas are characterised by increased infiltration of CD161 + iNKT cells and CD4 + T-cells, producing IL22 and IL13. These pro-inflammatory cytokines are likely important drivers of ECM dysregulation and tissue remodelling in perianal fistulizing disease.